Genre Based Approach Using Digital Story Telling to Enhance EFL Learners' Speaking Achievment - Fajar Kurniasih; Flora; Ujang Suparman (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This research set out to examine whether or not students' speaking achievement improved significantly after instruction in the Genre Based Approach (GBA) using Digital Story Telling (DST). The data in this research were obtained from the pretest and post-test. Thirty students from Senior High School were surveyed utilizing speaking exams to get the data. Five factors were considered while assessing the speaker's performance: grammar, vocabulary, fluency, comprehension, and pronunciation. This study used paired t-tests to examine the data. After the treatment, the speaking scores of the pupils showed a statistically significant improvement (p < 0.001). In addition, the results showed that the two most noticeable areas of speaking that improved the most were fluency and grammar. These results provide further evidence that the Genre-Based Approach using Digital Storytelling works to improve students' speaking skills.